Experimental performance investigation on the arrangement of metal foam as flow distributors in proton exchange membrane fuel cell. (1st March 2021) - Wan, Zhongmin; Sun, Yun; Yang, Chen; Kong, Xiangzhong; Yan, Hanzhang; Chen, Xi; Huang, Taiming; Wang, Xiaodong
Highlights: The arrangement of metal foam flow field in PEMEC was investigated experimentally. Metal foam is more suitable to be used in the anode side alone at RH = 1 condition. Metal foam in the cathode side leads to serious performance deterioration. Improved maximum power density is 36.2% by comparing with parallel channel. Abstract: Due to the elimination of 'land/channel' geometry in conventional bipolar plates, metal foam as flow distributor in proton exchange membrane fuel cell (PEMFC) has shown great potential in improving the uniformity of reactant and temperature distributions, which is beneficial to the performance enhancement of the fuel cell. However, the arrangement of metal foam which can be optimized to further enhance the performance of PEMFC has not been considered yet. In the study, nickel metal foam is used as a new type of flow field for experimental research, and compared with the performance of conventional graphite parallel flow field (case 1) in a PEMFC. With respect to the arrangement of metal foam, three cases, namely the use of metal foam either in the anode side (case 2) or cathode side (case 3), and the simultaneous use of metal foam in both sides (case 4), were designed. Experimental results showed that nickel metal foam flow field can make the temperature distribution at the membrane more uniform, which is conducive to the durability of the membrane, and improves the fuel utilization rate. By comparing with case 1 at fully humidified condition, the increase of maximal power density for case 2 is 15.67 %, which is higher than case 3 (6.36 %) and case 4 (9.09 %), indicating the importance of the arrangement of metal foam. The interpretation is that when relative humidity (RH) is high, the cathode side using nickel metal foam flow field is more prone to flooding. Furthermore, a 3-hour constant current test on case 1–4 indicated that at RH = 1, a serious voltage deterioration was observed after 105 min when nickel metal foam is used in the cathode side. With the decrease of RH, the critical flooding time was gradually postponed. This finding is especially useful for the practical applications of metal foam as flow distributor in a PEMFC.